Uloma (Uloma) metogana Ren, 2004: redescription of the adult and descriptions of the larva and pupa (Coleoptera: Tenebrionidae, Ulomini) - Liu, Shan-Shan; Li, Xiu-Min; Ren, Guo-Dong (Zootaxa, 2022)
The adult of Uloma (Uloma) metogana Ren, 2004, an endemic species to the southeastern Qinghai-Xizang Plateau of China, is redescribed and illustrated. The male of this species is newly discovered, its larva and pupa are described and illustrated for the first time. Meanwhile, sequences of three gene fragments (COI, Cytb and 16S rDNA) are obtained for the larva, pupa and adult to further confirm their identity.